Implementation of the Sahla Method in Qur’an Memorization - Zainal Arifin; Nur Lailatur Rohmah; Maryam Sulaeman; Christian Kuswibowo; Dian Febrianingsih (STAI Miftahul Ula Nganjuk, 2025)
The Sahla Method, implemented since 2020, plays a crucial role in building a generation of Qur’anic memorizers who are not only strong in memorization but also excel in recitation and application, following the correct pronunciation (makharij al-huruf) and tajwid rules. The memorization process is carried out with a tahsin class system, the use of bayati tones, as well as a memorization system for page numbers and verse positions. This study aims to analyze the implementation of the Sahla Method in memorizing the Qur'an at the Al-Imam Tiru Kidul Modern Tahfidz Pond, Gurah, Kediri. The research method used is descriptive research with a qualitative approach, involving interviews, observations, and documentation. The results of the study show that the application of the Sahla Method significantly improves the quality of reading and memorization of students, with many students successfully participating in and winning various Tahfidz competitions. The method ensures high-quality memorization, including the ability to recall page numbers, verse numbers, positions, and verse comprehension, in an enjoyable manner. This research is based on the Al-Imam Modern Tahfidz Boarding School, which educates students at the elementary, middle, and high school levels. The study was conducted in response to the increasing interest of parents in enrolling their children in this boarding school.